Brushless valve electric drive with minimum equipment excess for autonomous floating vehicle - Volyanskaya, Ya.B.; Volyanskiy, S.M.; Onischenko, O.A. (Електротехніка і електромеханіка, 2017)
Purpose. Development of a brushless valve electric drive with a minimum apparatus excess for an autonomous floating vehicle.
Methodology. The construction of models of an automated electric drive with a contactless DC motor and the subsequent
technical implementation of such automated electric drive under various control methods are possible using coordinate
transformations of differential equations describing the electric motor under the assumed assumptions. Results. The analysis of
the current state of an automated electric drive with a brushless DC motor in a special technique is carried out, possible directions
for the improvement of automated electric drives are determined. A simple technical solution of an automated electric drive with a
brushless DC motor was proposed and its mathematical model for an electric drive of an automatic floating vehicle with improved
technical and economic parameters was developed. Model of an automated electric drive with a brushless DC motor are carried
out. Originality. A simple technical solution for the construction of an automated electric drive with a brushless DC motor is
proposed, which excludes the use of intermediate computation of coordinates and an expensive encoder. Practical value. Model of
the proposed scheme of an automated electric drive with a minimum hardware redundancy, which confirmed the operability of
the proposed solution, were carried out. Analysis of the dynamic and static characteristics of the proposed scheme of an
automated asynchronous electric drive with a brushless DC motor with a simplified rotor position sensor has made it possible to
determine the maximum speed control range with an allowable level of its pulsations. Предложено простое схемотехническое решение построения автоматизированного электропривода (АЭП) с
бесконтактным двигателем постоянного тока (БДПТ), отличающееся исключением промежуточных программноаппаратных преобразований координат, широтно-импульсного модулятора, двух регуляторов тока и
высокоразрядного энкодера. Проведено компьютерное моделирование предложенной модификации АЭП с БДПТ и
показана его работоспособность в заданных диапазонах регулирования скорости. На основании результатов
моделирования АЭП с БДПТ обоснована возможность его применения в автономных плавательных аппаратах.